Use of metakaolin on enhancing the mechanical properties of self-consolidating concrete containing high percentages of crumb rubber. (1st July 2016) - Ismail, Mohamed K.; Hassan, Assem A.A.
Abstract: This research aimed to investigate the mechanical properties of self-consolidating rubberized concrete (SCRC) mixtures with high percentages of crumb rubber (CR). The effect of metakaolin (MK) compared to other supplementary cementing materials (SCMs) on enhancing the mechanical properties and stability of SCRC mixtures was highlighted in this research. The variables were percentage of CR (0–50% by volume of sand), type of SCM (fly ash, slag, and metakaolin), binder content (500–550 kg/m 3 ), coarse aggregate size (10–20 mm), and air entrainment. The mechanical properties of the tested mixtures were investigated based on their compressive strength, flexural strength, splitting tensile strength, and modulus of elasticity. The results indicated that using MK improved the mixture stability and particle suspension, which facilitated the development of SCRC mixtures with a high percentage of CR (30%) and with enhanced mechanical properties. Adding entrained air to SCRC mixtures with MK further enhanced the fresh properties and stability, and allowed a higher percentage of CR (40%) to be used safely in SCRC with acceptable stability/strength and with a density of less than 2100 kg/m 3 . The results also indicated that although SCRC mixtures had slightly higher mechanical properties compared to vibrated rubberized concrete (VRC), the problems associated with the fresh properties and stability of SCRC mixtures were reduced in VRC, which allowed up to 50% CR to be used in this mixture with acceptable stability/strength and with further reduction of the mixture density (less than 2050 kg/m 3 ). Highlights: The mechanical properties of SCRC were investigated. Effect of Metakaolin on enhancing the stability and strength was highlighted. Performance of vibrated rubberized concrete was investigated for comparison. Metakaolin improved the mixture stability and particle suspension. Up to 40% crumb rubber can be used in SCRC with Metakaolin.